Improving Students' Knowledge of Breakfast Energy and Protein Consumption through E-Booklet Media - Riyadi, Bastianus Doddy; Ayu, Pony Puspa; Hadisuyitno, Juin (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Malnutrition remains an important health issue in Indonesia, especially among undernourished children. The current nutrition intervention program, Family Nutrition Awareness, emphasizes the importance of breakfast in combating malnutrition. The purpose of this study was to determine the differences in maternal knowledge, energy, and protein consumption of students before and after counseling on breakfast using e-booklet media. This study used a pre-experimental type with a one-group pretest-posttest design. Maternal knowledge was assessed through a questionnaire, and energy and protein consumption was measured using a food recall form. The statistical analysis used was the paired T-test for normally distributed data and the Wilcoxon test for non-normally distributed data. The results showed significant differences in maternal knowledge and children's energy and protein intake before and after the e-booklet-based educational intervention (p=0.002 and p=0.000). This shows the effectiveness of e-booklets as a nutrition education media, which has the potential to positively influence maternal knowledge and improve children's breakfast habits. In conclusion, there is a difference in nutritional knowledge, energy, and protein consumption before and after counseling on breakfast using e-booklets. This study emphasizes the importance of innovative and accessible educational tools in combating malnutrition in Indonesia.